1994
DOI: 10.1037/1040-3590.6.3.218
|View full text |Cite
|
Sign up to set email alerts
|

Validation of malingered amnesia measures with a large clinical sample.

Abstract: A large sample of chronic postconcussive patients with and without overt malingering signs was compared with objectively brain-injured patients on common episodic memory and malingered amnesia measures. Probable malingerers and traumatically brain-injured subjects were not differentiated on popular episodic recall tests. In contrast, probable malingerers performed poorly on the Rey 15-Item, Rey Word Recognition List, Reliable Digit Span, Portland Digit Recognition Test, and Rey Auditory Verbal Learning Test re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
287
1
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 637 publications
(297 citation statements)
references
References 31 publications
6
287
1
3
Order By: Relevance
“…The nature of his mild complicated concussion was consistent with a composite MN-BEST rating of '15'. [34]), but performances on other effort measures were within normal limits. Pre-morbid level of intellect was within the average range (WTAR FSIQ = 91) and is relatively consistent with available WAIS-III intellectual performances.…”
Section: Blast Exposure Assessmentmentioning
confidence: 99%
“…The nature of his mild complicated concussion was consistent with a composite MN-BEST rating of '15'. [34]), but performances on other effort measures were within normal limits. Pre-morbid level of intellect was within the average range (WTAR FSIQ = 91) and is relatively consistent with available WAIS-III intellectual performances.…”
Section: Blast Exposure Assessmentmentioning
confidence: 99%
“…To control for lack of effort in the neuropsychological assessment, we calculated the Reliable Digit Span (RDS; Greiffenstein et al, 1994) as an embedded performance validity test. The RDS is calculated as the sum of the longest number of digits correctly repeated in the forward and backward condition of the Digit Span test of the Wechsler Adult Intelligence Scale Version III (Von Aster et al, 2006).…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%
“…RDS was originally developed by Greiffenstein et al [43] and has been shown to be a useful validity marker across a number of studies [22,41,44]. A cut-off score of less than 7 was used.…”
Section: Methodsmentioning
confidence: 99%